Pengaruh Likuiditas, Profitabilitas dan Leverage Terhadap Nilai Perusahaan pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2015–2018 - Santi Andrianti; Siti Ruhana Dara (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the Effect of Liquidity, Profitability and Leverage, on Firm Value. The method used in this research is panel data regression method. The sampling method is purposive sampling method. The sample studied 14 food and beverage companies. The results showed that liquidity has a tcount of 1.158838 <ttable 2.00575, it can be interpreted that liquidity has no significant effect on firm value which means H1 is rejected. Profitability has a tcount of -0.77472 <ttable 2.00575, so it can be interpreted that profitability has no significant effect on the value of the company which means H2 is rejected. Leverage has a tcount of 4.898083> t table 2.00575, so it can be interpreted that leverage has a significant effect on the value of the company, which means that H3 is accepted. Simultaneously H4 in this study was accepted, which means liquidity, profitability and leverage significantly influence the value of the company with an Adjusted R Square value of 85.06% and the remaining 14.93%.